2004
DOI: 10.1111/j.1365-246x.2004.02229.x
|View full text |Cite
|
Sign up to set email alerts
|

Palaeomagnetism of the Upper Carboniferous-Lower Permian transition from Paganzo basin, Argentina

Abstract: S U M M A R YA palaeomagnetic study of Upper Palaeozoic rocks was performed on Paganzo basin, centralwestern Argentina and its western extension, Río Blanco subbasin. The volcanic-volcaniclastic Río del Peñón and marine sedimentary Punta del Agua formations were sampled in the Rincón Blanco syncline. Both units represent the Upper Carboniferous-Lower Permian transition according to palaeontological and geochronological evidence. The Chancaní and Cerro ColoradoCaminiaga formations were sampled in their type loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Some poles from the Andean Cordillera [e.g., Jesinkey et al, 1987;Gilder et al, 2003;Rakotosolofo et al, 2006] were included in recent compilations even though they have undergone a complex kinematic evolution, including vertical axis rotations [Somoza and Tomlinson, 2002;Geuna and Escosteguy, 2004;Arriagada et al, 2008;Henry et al, 2016]. For this reason, poles from the Andean Cordillera were not included in this contribution.…”
Section: 1002/2016gc006692mentioning
confidence: 99%
“…Some poles from the Andean Cordillera [e.g., Jesinkey et al, 1987;Gilder et al, 2003;Rakotosolofo et al, 2006] were included in recent compilations even though they have undergone a complex kinematic evolution, including vertical axis rotations [Somoza and Tomlinson, 2002;Geuna and Escosteguy, 2004;Arriagada et al, 2008;Henry et al, 2016]. For this reason, poles from the Andean Cordillera were not included in this contribution.…”
Section: 1002/2016gc006692mentioning
confidence: 99%
“…To the north, the Neogene strata in the Traslasierra Valley (Figure B) are best exposed at the Nono fault exposure, where there are ~12 m of Pliocene and ~4 m of Pleistocene strata exposed [ Kraemer et al ., ]. Farther west, the range‐bounding Pocho fault is mostly covered by vegetation and modern alluvial fan and aeolian sediment [ Carignano , ], but local exposures of footwall strata contain folded Carboniferous strata overlain by Quaternary strata [ Geuna and Escosteguy , ]. The thickness of the Quaternary strata in the basin west of the Sierra de Pocho has not been well constrained.…”
Section: Surface Fault Observationsmentioning
confidence: 99%
“…Smith (1997), however, suggested that it is not necessary to postulate that the Earth had marked non-dipole components, and Kent and Olsen (2000) demonstrate a strong correlation between magnetic paleolatitudes and lithofacies distributions, in support of the notion of a dipolar field. In contrast, Geuna and Ecostegui (2003) recently have suggested that the misfit in some Late Paleozoic PPs of Argentina is due to local tectonic rotation of the sampling areas around a vertical axis.…”
Section: Introductionmentioning
confidence: 81%